Organophosphorus flame retardants in breast milk from Beijing, China: Occurrence, nursing infant's exposure and risk assessment - Chen, Xuelei; Zhao, Xuezhen; Shi, Zhixiong (The Science of the total environment, 2021)
Organophosphorus flame retardants (OPFRs) are widely used chemicals, whereas data on OPFRs in human being is limited. In this study, thirteen OPFRs were measured in 105 breast milk samples collected from Beijing mothers in 2018. The ∑13OPFRs ranged from <LOD to 106 ng mL−1 (<LOD-6700 ng g−1 lipid weight (lw)), with a median value 10.6 ng mL−1 (157 ng g−1 lw). The most abundant compound was tris(2-ethylhexyl) phosphate (TEHP), followed by triphenyl phosphate (TPhP) and 2-ethylhexyl diphenyl phosphate (EHDPP). The detecting frequencies and contamination levels of OPFRs in our study were higher than those reported in other studies, which indicated that China is one of the most affected regions by OPFRs. In addition, OPFR levels in our study were found to be higher than levels of brominated flame retardants (BFRs) in human milk from China. Based on regression analyses, mothers' personal characters, including age, pregnancy, residing/working location, and educational level were found to be impact factors of some OPFRs in breast milk. Estimated daily intakes (EDI) of the OPFRs for nursing infants via human milk ingest were calculated, and the mean EDIs of the 13 OPFRs ranged from 2.62 to 1640 ng kg−1 bw d−1. Since the mean and max EDIs of most OPFRs were lower than corresponding reference doses (RfDs), the daily OPFR intake for most nursing infants would not cause significant health concerns. However, the max EDIs of two OPFRs, TPhP and EHDPP, with values of 1.09 × 104 and 2190 ng kg−1 bw d−1, respectively, were higher than their corresponding RfDs. To our knowledge, this is the first report on the occurrence of OPFRs in human milk from China. [Display omitted] •Thirteen OPFRs were measured in 105 human milk samples collected in Beijing, China.•High detecting frequencies of OPFRs were found in human milk from Beijing, China.•Levels of OPFRs in breast milk from Beijing were higher than other countries.•Levels of OPFRs were obviously higher than BFRs in breast milk from China.•Daily OPFR intakes for infants via breastfeeding would not cause health risks.